Friends and foes: Extracellular vesicles in aging and rejuvenation - Brian V. Lananna; Shin‐ichiro Imai (FASEB BioAdvances, 2021)
Abstract Extracellular vesicles (EVs) are released by many different cell types throughout the body and play a role in a diverse range of biological processes. EVs circulating in blood as well as in other body fluids undergo dramatic alterations over an organism's lifespan that are only beginning to be elucidated. The exact nature of these changes is an area of active and intense investigation, but lacks clear consensus due to the substantial heterogeneity in EV subpopulations and insufficiencies in current technologies. Nonetheless, emerging evidence suggests that EVs regulate systemic aging as well as the pathophysiology of age‐related diseases. Here, we review the current literature investigating EVs and aging with an emphasis on consequences for the maintenance of human healthspan. Intriguingly, the biological utility of EVs both in vitro and in vivo and across contexts depends on the states of the source cells or tissues. As such, EVs secreted by cells in an aged or pathological state may impose detrimental consequences on recipient cells, while EVs secreted by youthful or healthy cells may promote functional improvement. Thus, it is critical to understand both functions of EVs and tip the balance toward their beneficial effects as an antiaging intervention.